1976
DOI: 10.1677/joe.0.0690227
|View full text |Cite
|
Sign up to set email alerts
|

Androstenedione and the Control of Luteinizing Hormone in the Ewe During Anoestrus

Abstract: Androstenedione and oestradiol were measured by radioimmunoassay in the utero-ovarian venous plasma of two ewes during anoestrus. The concentrations of both steroids were significantly higher than the corresponding concentrations in peripheral plasma, indicating that androstenedione and oestradiol are secreted by the ovary during anoestrus. The concentration of LH during anoestrus was measured by radioimmunoassay in jugular venous plasma of control ewes, ewes immunized against 11alpha-OH-androstenedione-bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 27 publications
3
54
1
Order By: Relevance
“…The mean secretion of each group was compared to that of controls by Student's t-test. For analysis of LH secretion by the pituitary gland, it has been accepted that pulsatile secretory episodes are reflected in transitory elevations of the hormone levels in plasma (Lincoln 1976;Martensz et al 1976). In the present study, a secretory episode was identified when a sample value exceeded the level of the previous sample by at least two standard deviations of the assay value of the previous sample.…”
Section: Analysis Of Resultsmentioning
confidence: 75%
“…The mean secretion of each group was compared to that of controls by Student's t-test. For analysis of LH secretion by the pituitary gland, it has been accepted that pulsatile secretory episodes are reflected in transitory elevations of the hormone levels in plasma (Lincoln 1976;Martensz et al 1976). In the present study, a secretory episode was identified when a sample value exceeded the level of the previous sample by at least two standard deviations of the assay value of the previous sample.…”
Section: Analysis Of Resultsmentioning
confidence: 75%
“…of animals indicated in (Scaramuzzi et ai, 1977 ;Van Look et ai, 1978;Scaramuzzi et ai, 1980a). Immunization against androstenedione increases the frequency of luteinizing hormone (LH) discharges and mean levels of LH in ewes (Martensz, Baird, Scaramuzzi & Van Look, 1976) in conjunction with increasing the number of follicles > 3 mm in diameter and ovulation rate (Scaramuzzi et ai, 1980a). A lack of significant differences in peripheral androstenedione or oestrogen concentrations between immunized (Groups III and IV) and control (Groups I and II) heifers in this study may be related to the relatively low titres (1:100 and 1:1000) acquired in the short immunization period (< 150 days).…”
Section: Characterization Of the Antiserummentioning
confidence: 99%
“…The concentration of LH was determined by radioimmunoassay (Martensz, Baird, Scaramuzzi & Van Look, 1976) of duplicate quantities of plasma and results were expressed in terms of ng NIH-LH-S14/ml. The sensitivity of the assay was 0-3 ng/ml and the intra-and inter-assay coefficients of variation were 8 and 10% respectively.…”
Section: Radioimmunoassaysmentioning
confidence: 99%